EVALUASI DAN PENGEMBANGAN SISTEM PENILAIAN KINERJA PADA PT HKS - Wijayanti, Annisa; Wimbrati, Supra (Faculty of Psychology, Diponegoro University, 2012)
Performance appraisal is a systematic, formal and evaluative description about employee’s work quality to standardize an individual or team work behavior. It is an important system and process to personnel and human resource management. When communicated inappropriately, it can impede the organization success and employees’ chance in planning their career with the company where they work. This research aimed to evaluate and develop existed performance appraisal system and described the process of development appraisal system of retail and marketplace. Interviews, observations, and company’s documents were conducted to gather empirical information regarding the needs of developing new appraisal system. Grote’s performance management strategy was used to analyze the evaluation and development which produced a new performance appraisal system and enabled to mapping employee’s ability for their promotion’s opinion.Keywords: evaluation and development, performance appraisal system, retail and marketplace